Evaluation of Vegetables Shelf Life Using Multispectral Scattering Method - Faisal Abdullah (Jurnal Natural, 2014)
This study was aimed to develop an algorithm based on the optical properties of some selected vegetables which can be used to evaluate shelf- life of some selected vegetables using multispectral scattering method. Multispectral algorithm will be developed to correlate light backscattering radiation of a vegetable with the level of shelf life conditions. The partial least square (PLS) regression models using three wavelengths were used to estimate the shelf life changes of the vegetable samples. The results showed that the developed multispectral scattering algorithms can be used to evaluate the shelf life changes of Chinese cabbage, carrot, chili, and cucumber using wavelengths at 880, 890, and 950 nm as the light sources respectively.  The calibration and validation processes of the algorithm produced good accuracy measurements as represented by high R2 values and low Root Mean Square Error (RMSE). For the Chinese cabbage and the carrot samples, the algorithm was not effective to predict the changes of the shelf life because the responses was kept increasing even after the samples were dried and deteriorated. Also, the algorithms cannot be used to evaluate the shelf life changes of the onion because the calibration and validation processes produced low accuracy of measurements.